Constitutively active RAS signaling reduces 1, 25 dihydroxyvitamin D-mediated gene transcription in intestinal epithelial cells by reducing vitamin D receptor expression. Issue 173 (October 2017) - DeSmet, Marsha L.; Fleet, James C.
Highlights: Activated RAS signaling reduces vitamin D mediated gene expression in intestinal epithelial cells. Activated RAS signaling reduced Vitamin D Receptor (VDR) level in intestinal epithelial cells. Chromatin accessibility at multiple regulatory sites in the VDR gene is reduced by RAS activation in intestinal epithelial cells. Abstract: High vitamin D status is associated with reduced colon cancer risk but these studies ignore the diversity in the molecular etiology of colon cancer. RAS activating mutations are common in colon cancer and they activate pro-proliferative signaling pathways. We examined the impact of RAS activating mutations on 1, 25 dihydroxyvitamin D (1, 25(OH)2 D)-mediated gene expression in cultured colon and intestinal cell lines. Transient transfection of Caco-2 cells with a constitutively active mutant K-RAS (G12 V) significantly reduced 1, 25(OH)2 D-induced activity of both a human 25-hydroxyvitamin D, 24 hydroxyase (CYP24A1) promoter-luciferase and an artificial 3X vitamin D response element (VDRE) promoter-luciferase reporter gene. Young Adult Mouse Colon (YAMC) and Rat Intestinal Epithelial (RIE) cell lines with stable expression of mutant H-RAS had suppressed 1, 25(OH)2 D-mediated induction of CYP24A1 mRNA. The RAS effects were associated with lower Vitamin D receptor (VDR) mRNA and protein levels in YAMC and RIE cells and they could be partially reversed by VDR overexpression. RAS-mediated suppression of VDR levels was not due to either reduced VDR mRNA stability or increased VDR gene methylation. However, chromatin accessibility to the VDR gene at the proximal promoter (−300 bp), an enhancer region at −6 kb, and an enhancer region located in exon 3 was significantly reduced in RAS transformed YAMC cells (YAMC-RAS). These data show that constitutively active RAS signaling suppresses 1, 25(OH)2 D-mediated gene transcription in colon epithelial cells by reducing VDR gene transcription but the mechanism for this suppression is not yet known. These data suggest that cancers with RAS-activating mutations may be less responsive to vitamin D mediated treatment or chemoprevention.